Pengaruh Gaya Kepemimpinan dan Profesionalisme Melalui Motivasi Kerja Terhadap Kinerja Guru di Sekolah Menengah Atas Negeri 1 Merangin - Nopen Asri; Pantun Bukit; Osrita Hapsara (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study is to describe the leadership style, professionalism, work motivation and teacher performance in State High School 1 Merangin and to analyze the influence of leadership style and professionalism partially and simultaneously directly and indirectly on work motivation and employee performance, as well as to analyze work motivation on employee performance. To answer the purpose of this research, this research is supported by theoretical studies related to research variables, namely leadership style, professionalism, work motivation, and performance. In addition, the author is also looking for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this study is teachers of SMAN 1 Merangin which amounts to 50 teachers with conditions in 2022. The data analysis technique used in this study is through path analysis followed by hypothesis testing through F test (Simultaneous) and t test (Partial). From the path analysis testing conducted, it was found that leadership style and professionalism have an influence on work motivation and teacher performance, both directly and indirectly. This explains that if the organization has a good leadership style and better professionalism, this will further increase teacher motivation for the organization and provide maximum work results. This study concluded that the leadership style, professionalism, work motivation and performance of SMAN 1 Merangin teachers are in good condition. In addition, leadership style and professionalism partially and simultaneously have a positive and significant influence on work motivation and teacher performance at SMAN 1 Merangin. Similarly, work motivation has a positive and significant influence on teacher performance.